PERJANJIAN PENGIKATAN JUAL BELI ATAS TANAH BERDASARKAN SURAT KETERANGAN GANTI RUGI DI KABUPATEN KAMPAR - Rahmatika Hakim, Tia; Warman, Kurnia; Syofyan, Syofirman (Universitas Ekasakti, 2023)
Sale and purchase binding agreement, of course, a notary can provide legal counseling, namely by explaining to the parties, that the binding sale and purchase agreement made should be based on a land certificate, because the ownership of a certificated land right has been registered at the Land Office which has legal certainty, protection law and can prove himself as the holder of the land rights. However, in practice, the binding sale and purchase agreement in Kampar Regency is made using a letter of compensation (SKGR) so it is very straightforwardproblems to occur which can cause losses. The method used is empirical juridical which emphasizes the reality in the field associated with legal aspects or applicable laws and regulations regarding the object of research. The binding sale and purchase agreement should be made using a land certificate instead of using a letter of compensation and based on its authority the notary should be able to provide legal counseling to the parties before the binding sale and purchase agreement is made so that the urgent sale and purchase agreement can be carried out properly.